The effect of string tension on shuttlecock velocity - Vanasant, T.; Mingkhumlert, S.; Limroongreungrat, W. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Badminton players currently lack of knowledge and understanding about the effect of tension on hitting performance. This study aimed to investigate the effect of string tension on shuttlecock velocity. The experiments were performed by stringing 5 racquets with automatic machine and assigned pull tension at 22, 24, 26, 28 and 30 lbs/ft2, respectively. The racquets were set up in the system with motor speed adjusted at 450 rpm. Then, each racquet was conducted to hit 10 times and capture with 2 high speed cameras at 2,000 frame/sec. Five screenings were made as to search a perfect hitting to analyze shuttlecock speed. The statistic comparison uses one way-ANOVA and repeated measure. The result shows that shuttlecock velocity depends on string tension, that is, lower tension generates more shuttlecock velocity than high tension (22>24>26>28>30). Therefore, badminton players should be have an understanding and modify their stringing behavior to suit each individual.